If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -5) + 4 = 56 Reorder the terms: 2(-5 + m) + 4 = 56 (-5 * 2 + m * 2) + 4 = 56 (-10 + 2m) + 4 = 56 Reorder the terms: -10 + 4 + 2m = 56 Combine like terms: -10 + 4 = -6 -6 + 2m = 56 Solving -6 + 2m = 56 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2m = 56 + 6 Combine like terms: -6 + 6 = 0 0 + 2m = 56 + 6 2m = 56 + 6 Combine like terms: 56 + 6 = 62 2m = 62 Divide each side by '2'. m = 31 Simplifying m = 31
| x-2x=41/2 | | 3x=-y+7 | | .83t+4=.16t-2 | | 11-8x=9x-7x-19 | | -2(5w-5)+6w=5(w+5) | | 9+4y=98 | | 32+5=13 | | 500-133x=500 | | 9x*-4*4= | | 10x^2-41x+32=0 | | 5m^2+60m+163=3 | | 56+90+x=180 | | 4x^2-60x-400=0 | | g(x)=x^2+10x | | 3(w-6)-6=-6(-3w+2)-6w | | 5(4x-4)=8x+28 | | (4v+9)(1-V)=0 | | -13=5(1+4m)-1m | | u=-3v+15 | | 2x-22=2x+10 | | -7x+13=5+13x | | 81/-9= | | -9v-22=-4(v-7) | | 3+s(k+1)=3k+6 | | 7x-4=5(x-1)+35 | | 8(4+6n)=-18-2n | | -14=2(u+8)-8u | | 16+23+x=180 | | u-5=21 | | 8+c=-45 | | -10=-7w+5(w-6) | | 5x+5-2x=4x-7 |